2021
DOI: 10.1186/s12974-021-02166-3
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 reverses phenotypic polarization of glial cells and cognitive impairment via negative regulation of NF-κB signaling axis in APP/PS1 mice

Abstract: Background Thymosin β4 (Tβ4) is the most abundant member of the β-thymosins and plays an important role in the control of actin polymerization in eukaryotic cells. While its effects in multiple organs and diseases are being widely investigated, the safety profile has been established in animals and humans, currently, little is known about its influence on Alzheimer’s disease (AD) and the possible mechanisms. Thus, we aimed to evaluate the effects and mechanisms of Tβ4 on glial polarization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Electroacupuncture, a widely used Chinese traditional therapy, improved learning, and memory of AD rats, inhibited the activation of glia and polarized microglia toward M2 phenotype in hippocampus of AD rats with decreased pro-inflammatory cytokines and increased anti-inflammatory cytokines by inhibiting NF-κB pathway but activating STAT-6 pathway ( Xie et al, 2021 ). Over-expression of thymosin β4 (Tβ4), a constituent part of cytoplasm and cytoskeleton, improved neuronal function and cognitive ability, reduced brain Aβ accumulation, upregulated insulin-degrading enzyme, and alleviated neuroinflammatory response by converting microglia and astrocyte to neuroprotective phenotype in APP/PS1 mice via negative regulation of TLR4/MyD88/NF-κB p65 and p52 pathways ( Wang et al, 2021 ).…”
Section: Other Factors Inducing Microglia Polarization In Neurodegene...mentioning
confidence: 99%
“…Electroacupuncture, a widely used Chinese traditional therapy, improved learning, and memory of AD rats, inhibited the activation of glia and polarized microglia toward M2 phenotype in hippocampus of AD rats with decreased pro-inflammatory cytokines and increased anti-inflammatory cytokines by inhibiting NF-κB pathway but activating STAT-6 pathway ( Xie et al, 2021 ). Over-expression of thymosin β4 (Tβ4), a constituent part of cytoplasm and cytoskeleton, improved neuronal function and cognitive ability, reduced brain Aβ accumulation, upregulated insulin-degrading enzyme, and alleviated neuroinflammatory response by converting microglia and astrocyte to neuroprotective phenotype in APP/PS1 mice via negative regulation of TLR4/MyD88/NF-κB p65 and p52 pathways ( Wang et al, 2021 ).…”
Section: Other Factors Inducing Microglia Polarization In Neurodegene...mentioning
confidence: 99%
“…Cognitive deficit is a defining characteristic of AD. APP/PS1 mice are widely used in AD research ( Wang M. et al, 2021 ) because they model well the pathological changes of AD such as senile plaque, neuronal deletion, amyloid-associated inflammation and cognitive decline. It was shown that APP/PS1 mice developed learning and memory deficits at 6 months of age ( Webster et al, 2014 ), which is now considered to be the early stage of AD in this model.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 agonists can activate MyD88-dependent intracellular signaling pathways, leading to the translocation of NF-κb. Phosphorylation of NF-κb results in its activation and translocation into the nucleus, where it mediates a series of downstream reactions, especially oxidative stress and neuroin ammation [37][38][39]. Phosphorylation of p65 is a marker of NF-κb activation.…”
Section: Discussionmentioning
confidence: 99%